ANALYSIS OF PREVENTION BEHAVIORS OF PULMONARY TUBERCULOSIS TRANSMISSION QUESTIONNAIRE (PBPTTQ) - Kusuma Wijaya Ridi Putra; Pipit Festi Wiliyanarti; Faida Annisa (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: Prevention of pulmonary tuberculosis transmission behavior is also one of the keys to the increased incidence of pulmonary tuberculosis. Unhealthy behavior in patients with pulmonary tuberculosis can be caused due to lack of information about TB in the community so that they lack responsibility for the tuberculosis transmission.Objective: This study aimed to analyze the Prevention Behaviors of Pulmonary Tuberculosis Transmission Questionnaire (PBPTTQ) to see whether this questionnaire can be used to assess habits in preventing pulmonary tuberculosis transmission in the community.Methods: The design used in this study was cross-sectional design. This study was conducted in the Public Health Center of Medokan Ayu, Surabaya. The sample in this study were 30 people with positive smear pulmonary tuberculosis who are in the working area of Public Health Center of Medokan Ayu, Surabaya. This study used Prevention Behaviors of Pulmonary Tuberculosis Transmission Questionnaire (PBPTTQ). PBPTTQ consists of 15 items with 11 items that are positive questions and 4 items that are negative questions. PBPTTQ using Likert Scale with 5-point rating scale. Data analysis of Prevention Behavior of Pulmonary Tuberculosis Transmission Questionnaire used statistical analysis using SPSS 21. Data analysis performed was mean, standard deviation, I-CVI, and Cronbach Alpha.Results: Prevention Behaviors of Pulmonary Tuberculosis Transmission Questionnaire (PBPTTQ) has a high enough reliability value marked by a Cronbach Alpha value of .639. In addition, the validity test of this questionnaire found that I-CVI = .84.Conclusion: Based on the results of the study, Prevention Behaviors of Pulmonary Tuberculosis Transmission Questionnaire (PBPTTQ) can be used to assess pulmonary transmission prevention behavior in the community. Key words: Prevention Behavior, pulmonary tuberculosis transmission, public health center, questionnaire.